The role of HR practices in knowledge intensive self-managed organizations : from management centricity towards human centricity - Moore, Sari (My University, 2021)
Today, many organizations are seeking to organize their operations more flexible and human centric manner than before. Old hierarchical models of organizing are no longer applicable when knowledge intensive services form a core business for many organizations. The role of competent workforce is essential in these organizations, and the role of customer come more and more significant because of co-value creation. A relative new attempt of organizing, a self-managed organization (SMO), responds the call of finding more human centric and dynamic forms of organizing. SMOs operate normally without any middle management and believe in shared power and shared leadership. They form social systems with evolutionary purpose. The purpose of this qualitative study was to explore the role of HR practices in knowledge intensive SMOs. The conducted research involved five narratives written CEOs or HR directors working at knowledge intensive firms. Narrators told a story on how the middle management duties are handled and what is the role of HR practices at their workplaces. The research analysis was conducted by using narrative analysis and analysis of narratives. The content of written narratives was under analysis. Study results were presented in a form of grand narrative, in which the essence of the content of five texts was summarized. Thematic analysis was then arranged to explore the correlation between strategic wellbeing and used HR practices in studied SMOs. The study material was organized in narrative specific categories under given themes. The used theoretical SHRM framework was general yet with variety of aspects due to the importance of various factors that affect the role of HR practices in knowledge intensive SMOs. As a conclusion, SMOs provide a prosperous setting for HR practices to bring out the strategic and managerial power embedded in these practices. SMOs are managed by employees collectively and employees lean on dynamic structures that build on HR practices and processes created and modified by very employees. Employee agency power is guided by variety of principles, models, duties, patterns, recommendations and so on. Unlike in traditional organizations where true agency power is granted for few individuals, used HR practices in SMOs directly affect work agency and work energy of employees. However, strategic power embedded in these practices is not fully understood nor it is expanded to cover customer work. Employees also handle many HR duties. The ideal future model of SHRM in SMOs that highlights the agency power of employees and customers, and the importance of strategic wellbeing is presented in the chapter of conclusions. The other significant findings were few. Firstly, there is no organization that is fully self-managed, becoming a SMO is more of a journey. Secondly, having unified overall organizational structure with dynamic structures, HR practices and processes, together with static structures – various teams – is challenging. HR as whole has a traditional status, and a model of organizing a SMO by Laloux, a teal organization, is thus commonly exploited. Thirdly, the dominance of management centricity and culture of dominance is spread all over the world and is taken as a proper form of organizing supported by conducted SHRM research and legislation. Yet, their dominance is collapsing whereas the number of SMOs most likely multiplies in the future because of the promising outcomes.

Nykyään useat yritykset haluavat järjestää toimintansa joustavammalla, tehokkaammalla ja ihmisläheisemmällä tavalla kuin ennen. Vanhat hierarkkiset organisointimallit eivät ole enää toimivia, kun tietotyöhön ja asiantuntijuuteen perustuvat palvelut muodostavat ydinliiketoiminnan useissa yrityksissä. Työvoiman rooli on keskeinen, ja asiakkaan toimijuuden merkitys lisääntyy, kun arvoa luodaan yhdessä. Uudehko organisoitumisen muoto, itseohjautuva organisaatio, vastaa liiketoimintaympäristöstä nousseeseen tarpeeseen ihmisläheisellä ja dynaamisella tavalla. Itseohjautuvissa organisaatioissa ei ole keskijohtoa. Nämä organisaatiot uskovat jaettuun valtaan ja johtajuuteen ja muodostavat sosiaalisia alati kehittyviä systeemejä. Tämän kvalitatiivisen tutkimuksen tarkoituksena oli valottaa HR-käytäntöjen roolia näissä itseohjautuvissa organisaatioissa. Tutkimus pohjasi viiteen itseohjautuvassa organisaatiossa työskentelevän joko toimitusjohtajan tai HR-johtajan kirjoittamaan narratiiviin. Kertojat pohtivat tekstissään, miten heidän kotiorganisaatiossaan korvattiin keskijohdon monet tehtävät ja mikä oli HR-käytäntöjen rooli. Analysoinnissa keskeistä oli narratiivien sisältö. Sisällöstä muodostettiin yksi yhteinen viiden tekstin keskeiseen sisältöön perustuva narratiivi. Lisäksi sisältöä analysoitiin ennalta muodostettujen strategiseen työhyvinvointiin linkittyvien teemojen mukaisesti. Teoreettinen strategiseen henkilöstöjohtamiseen keskittyvä viitekehys oli yleisluontoinen mutta laaja-alainen tutkittavaan ilmiöön liittyvien monien tekijöiden takia. Tutkimuksen mukaan ohjausvoima, joka HR-käytännöissä piilee, pääsee oikeuksiinsa itseohjautuvissa organisaatioissa. Työntekijät yhdessä ovat määräävässä asemassa itseohjautuvissa organisaatioissa, ja heidän toimintaansa ohjaavat dynaamiset rakenteet, yhteiset käytännöt, joita he itse luovat ja päivittävät. Työntekijän toimijuutta ohjaa monet periaatteet, mallit, toimintatavat, vastuut, suositukset jne. Toisin kuin hierarkkisissa johtajakeskeisissä organisaatioissa, joissa todellinen toimivalta on muutamilla, HR-käytännöt vaikuttavat siis välittömästi työntekijöiden energiaan ja toimijuuteen. HR-käytäntöjen strategista arvoa ei kuitenkaan täysin ymmärretä varsinkaan asiakastyössä. Työntekijät vastaavat myös HR-tehtävistä. Tutkielman johtopäätöksiä käsittelevässä luvussa esitetään strategisen henkilöstöjohtamisen ideaalinen malli itseohjautuvissa organisaatioissa. Mallissa korostuu asiakkaan ja työntekijän toimijuus ja strategisen hyvinvoinnin keskeinen rooli. Muita tärkeitä huomioita oli muutamia. Ensinnäkin mikään organisaatio ei ole täysin itseohjautuva, vaan itseorganisoituvaksi organisaatioksi tuleminen on taival. Toiseksi niin dynaamisten rakenteiden – HR-käytäntöjen toimivan kokonaisuuden – kuin mahdollistavien rakenteiden – erilaisten tiimien ja kokoonpanojen – yhdistäminen aiheuttaa haasteita itseohjautuvissa organisaatioissa. HR toimintona nähdään perinteisenä, ja Laloux’n teal-organisaatiomallia käytetään usein mallina organisoitumisessa. Kolmanneksi johtajakeskeisyys ja rationaalisuuden kulttuuri ovat itsestäänselvyyksiä, joita myös lainsäädäntö ja tehty tutkimus ovat ylläpitäneet. Niiden valta-asema on kuitenkin heikentymässä, kun taas lupaavien tulosten vuoksi itseohjautuvien organisaatioiden määrä tullee lisääntymään tulevaisuudessa.
Keywords: SHRM, management centricity, human centricity, SMOs, HR practices, strategic wellbeing, work agency, work energy, organizational culture, HR stakeholders